2018
DOI: 10.1080/10962247.2018.1443855
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the physical and chemical characteristics of fine road dust at different urban sites

Abstract: Size and chemical characteristics of fine road dust at sites having distinct urban characteristics were examined. Residential coal and biomass burning and traffic affected physiochemical properties of the fine road dust. Different road dust profiles at different sites should be needed to determine the ambient PM2.5 sources more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For the determination of elements, the filtered extract was digested with HNO 3 and HCl (3:1) and was concentrated in 0.5 mL using a microwave digester (Ethos 1600, Milestone, Shelton, CT, USA). The concentrated sample was reconstituted to 10 mL with a 2% HNO 3 solution, and the sample was introduced to an inductively coupled plasma mass spectrometer (ICP-MS) (7500CE, Agilent Technologies, Wilmington, DE, USA) to determine the elements: Al, As, Ba, Cd, Co, Cu, Fe, Mn, Ni, Pb, Sr, Ti, V, and Zn (Saxena et al 2017;Lee et al 2018).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For the determination of elements, the filtered extract was digested with HNO 3 and HCl (3:1) and was concentrated in 0.5 mL using a microwave digester (Ethos 1600, Milestone, Shelton, CT, USA). The concentrated sample was reconstituted to 10 mL with a 2% HNO 3 solution, and the sample was introduced to an inductively coupled plasma mass spectrometer (ICP-MS) (7500CE, Agilent Technologies, Wilmington, DE, USA) to determine the elements: Al, As, Ba, Cd, Co, Cu, Fe, Mn, Ni, Pb, Sr, Ti, V, and Zn (Saxena et al 2017;Lee et al 2018).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Further analysis showed that the back trajectories in CD were at a relatively higher altitude, leading to the characteristics of air flow at the receptor site more similar to that of source regions. The air parcels were mainly transported from Mongolia where dust and biomass burning were important sources [68,69]. In contrast, during pollution episodes, air masses As shown in Figure 4, primary sources were the predominant contributors to WSOC during different periods, accounting for 68% of WSOC on average, including biomass burning (22%), other combustion source (19%), industrial source (17%), coal combustion (7%), and dust (3%).…”
Section: Primary Sources Of Wsoc Determined By the Pmf Modelmentioning
confidence: 99%
“…The composition of fine dust varies from region to region (Lee et al 2018), and even in the same area, the composition of fine dust varies depending on the surrounding conditions, such as traffic volume, industrial emissions or the presence of incinerators. DNA damage can vary depending on the composition of fine dust.…”
Section: Introductionmentioning
confidence: 99%